2017
DOI: 10.3748/wjg.v23.i34.6212
|View full text |Cite
|
Sign up to set email alerts
|

Circulating inflammatory factors associated with worse long-term prognosis in colorectal cancer

Abstract: AIMTo investigate association of circulating inflammatory factors at the time of colorectal cancer (CRC) surgery with survival.METHODSPlasma levels from 174 CRC patients (69 females and 105 men), with median age 70 years (range 29-90), localized in the colon (n = 105) or rectum (n = 69), with stage I (n = 24), stage II (n = 54), stage III (n = 67) and stage IV (n = 29) were measured using commercially available Bio-Plex Pro™ Human Chemokine Panel 40-Plex, including 40 different chemokines, cytokines and interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
0
29
0
1
Order By: Relevance
“…Numerous articles had analyzed the relationship between inflammatory cytokines and the CRC progression and prognosis. Although the specific mechanism of action is still controversial, but it becomes a consensus among many researchers that the inflammatory response that accompanies cancers can induce and promote tumor progression [24][25][26] . It is now widely accepted that: Many tumor-promoting effects of "smouldering" inflammation in the tumor microenvironment play the carcinogenic role through external pathways (inflammatory environment that increases the risk of cancer) or internal pathways (genetic changes), which ultimately affect the proliferation and survival of malignant cells, promote angiogenesis and metastasis, destroy adaptive immune response, and change the response to hormones and chemotherapy drugs [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous articles had analyzed the relationship between inflammatory cytokines and the CRC progression and prognosis. Although the specific mechanism of action is still controversial, but it becomes a consensus among many researchers that the inflammatory response that accompanies cancers can induce and promote tumor progression [24][25][26] . It is now widely accepted that: Many tumor-promoting effects of "smouldering" inflammation in the tumor microenvironment play the carcinogenic role through external pathways (inflammatory environment that increases the risk of cancer) or internal pathways (genetic changes), which ultimately affect the proliferation and survival of malignant cells, promote angiogenesis and metastasis, destroy adaptive immune response, and change the response to hormones and chemotherapy drugs [27] .…”
Section: Discussionmentioning
confidence: 99%
“…So far, anecdotal evidence suggests that CXCL-13 together with CXCR5 might play increasingly vital roles in regulating tumor occurrence, progression, metastasis and prognosis in the microenvironment where the tumor is located [16][17][18][19]. Some recent studies have found that CXCL-13 has a predictive value for the prognosis of patients with CRC [20,21]. Besides those previous researches, the function of CXCL-13 in the response to CRC to 5-Fu-based chemotherapy and drug resistance remains a big mystery.…”
Section: Introductionmentioning
confidence: 99%
“…The role of metabolic markers such as leptin, adiponectin, IGF-1, and TNF-α in the progression of diseases is becoming more significant. Indeed several studies have previously reported the correlation of such markers, individually, with colorectal neoplasia in different populations ( 34 38 ). However, none of these studies have addressed the association of these metabolic markers combined with the risk of colorectal neoplasia in a African Americans a population with higher prevalence of obesity, diabetes and colon cancer than other ethnic groups in the US population.…”
Section: Introductionmentioning
confidence: 99%